2006
DOI: 10.1038/sj.onc.1209944
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the complexities of the NF-κB signalling pathway using mouse knockout and transgenic models

Abstract: The nuclear factor-jB (NF-jB) signalling pathway serves a crucial role in regulating the transcriptional responses of physiological processes that include cell division, cell survival, differentiation, immunity and inflammation. Here we outline studies using mouse models in which the core components of the NF-jB pathway, namely the IjB kinase subunits (IKKa, IKKb and NEMO), the IjB proteins (IjBa, IjBb, IjBe and Bcl-3) and the five NF-jB transcription factors (NF-jB1, NF-jB2, c-Rel, RelA and RelB), have been g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
276
2
3

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 287 publications
(290 citation statements)
references
References 190 publications
9
276
2
3
Order By: Relevance
“…27 This phenotype was reproduced in mice with constitutive global deletion of ikk␤ or NEMO, confirming that the IKK/NF-B system plays a critical role in hepatocyte survival, at least during embryogenesis. 28 At the same time, data from in vitro studies with human HCC cell lines consistently demonstrate that NF-B is cytoprotective via its ability to prevent apoptosis. Furthermore, the oncogenic HBV protein HBx and the HCV core and NS5B proteins were reported to induce NF-B.…”
Section: Nf-b As a Tumor Suppressor In Hepatocytesmentioning
confidence: 75%
“…27 This phenotype was reproduced in mice with constitutive global deletion of ikk␤ or NEMO, confirming that the IKK/NF-B system plays a critical role in hepatocyte survival, at least during embryogenesis. 28 At the same time, data from in vitro studies with human HCC cell lines consistently demonstrate that NF-B is cytoprotective via its ability to prevent apoptosis. Furthermore, the oncogenic HBV protein HBx and the HCV core and NS5B proteins were reported to induce NF-B.…”
Section: Nf-b As a Tumor Suppressor In Hepatocytesmentioning
confidence: 75%
“…In addition, specific C-terminal Ser to Ala mutations are sometimes included to reduce the constitutive turnover of IkBa (van Antwerp et al, 1996). Such SR molecules have been used successfully to inhibit NF-kB activity in a variety of in vitro cell culture studies (e.g., van Antwerp et al, 1996;Wang et al, 1996;Bushdid et al, 1998;Kanegae et al, 1998) and in several in vivo transgenic mouse studies (see Gerondakis et al, 2006). In general, the use of the IkBa-SR has been taken as one of the best evidences for the involvement of NF-kB in a given physiological process; however, because IkBa does not bind well to RelB-containing complexes, the IkBa-SR is probably primarily a blocker of the canonical NF-kB pathway.…”
Section: Ikb Super-repressorsmentioning
confidence: 99%
“…For example, as described above, IKKa and IKKb are active as dimers. However, they appear to have distinct physiological functions in that disruption of each IKK gene in mice leads to quite different phenotypes (Gerondakis et al, 2006). Furthermore, IKKa and IKKb can be activated independently by different upstream signals.…”
Section: Introductionmentioning
confidence: 99%
“…These stimuli may trigger inflammation, innate immune responses, adaptive immune responses, secondary lymphoid organ development and osteoclastogenesis. Studies with knockout mice have revealed NF-kB's critical involvement in all of these processes (Gerondakis et al, 2006). NF-kB was first identified as a biochemical activity capable of binding to a 10 base pairs (bp) sequence within the transcriptional enhancer of the immunoglobulin (Ig) k light chain gene.…”
Section: Introductionmentioning
confidence: 99%